TKI Resistance for T790M Mutation - Hong WANG (Chinese Journal of Lung Cancer, 2015)
Background and objective Epidermal growth factor receptor (EGFR) the development of orally activesmall molecule inhibitors for non-small cell lung cancer (NSCLC) provides anew treatment plan. EGFR gene mutation in patients with activation EGFR tyrosine kinase inhibitor (EGFR-TKIs) therapy for the treatment of sensitive, so that a large number of clinical benefit. The first generation of reversible ATP-competitive EGFR-TKIs, gefitinib and erlotinib as first-line, second-line or has the effect of maintenance therapy. Although the initial effect of these drugs have, but most patients will produce drug resistance. Within a year, 50%-60% patients had T790M housekeeping gene mutation associated with. Irreversible EGFR-TKIs recent background: afatinib and dac-omitinib covalent binding and inhibition of multiple ErbB family receptors (EGFR, HER2 and HER4). People evaluate these drugs as first-line treatment of significance, and acquired drug resistance situation significance on the first generation EGFR-TKIs. Afatinib is the first ErbB family approved blocking agent, used to treat with EGFR activatingmutations in patients with non small cell lung cancer; dacomitinib are in the later stages of clinicaldevelopment. EGFR inhibitors specifically targeting T790M resistance mutations (AZD9291, CO-1686, HM61713) are in the early stages of development. As discussed in this paper, the scope of the EGFR-TKIs kinase to target different, EGFR receptor binding was reversible and drug interaction potential is also different. For clinicians, these differences of the multi drug treatment of patients with non-small cell lung cancer with meaning, from the innovative anticancer drug combination therapy strategy point of view, these differences are also of great significance.